Challenges to the development of an entrepreneurial university ecosystem: The case of a Finnish university campus. Issue 2 (April 2019) - Lahikainen, Katja; Kolhinen, Johanna; Ruskovaara, Elena; Pihkala, Timo
The purpose of this study is to add to the literature on entrepreneurial university ecosystems by highlighting the ways in which academics engage or decouple in entrepreneurship processes and thereby in the emerging entrepreneurial ecosystem. The study extends our understanding of the emergence of an entrepreneurial university ecosystem by providing an in-depth analysis of a Finnish university campus, investigating how individuals' perceptions respond to societal and institutional demands for the fostering of entrepreneurship. The findings suggest that education and research are regarded as the highly institutionalized logics of universities, and these logics tend to be maintained since more rewards are associated with them than are associated with the logic of entrepreneurial actions. These competing logics lead to conflicting interests and cause intentional and unintentional decoupling in the adaptation and implementation of entrepreneurial actions in universities.